Core-dependent and ligand-dependent relativistic corrections to the nuclear magnetic shieldings in MH4-nYn (n=0-4; M = Si, Ge, Sn, and Y = H, F, Cl, Br, I) model compounds - Maldonado, Alejandro Fabian (2014)
The nuclear magnetic shieldings of Si, Ge, and Sn in MH 4−n Y n (M = Si, Ge, Sn; Y = F, Cl, Br, I and n=1-4)molecular systems are highly influenced by the substitution of one or more hydrogens by heavy-halogen atoms. We applied the linear response elimination of small components (LRESC) formalism to calculate those shieldings and learn whether including only a few of the leading relativistic correction terms is sufficient to be able to quantitatively reproduce the full relativistic value. It was observed that the nuclear magnetic shieldings change as the number of heavy halogen substituents and their weights vary, and the pattern of σ(M) generally does not exhibit the normal halogen dependence (NHD) behavior that can be seen in similar molecular systems containing carbon atoms. We also analyzed each relativistic correction afforded by the LRESC method and split them in two: core-dependent and ligand-dependent contributions; we then looked for the electronic mechanisms involved in the different relativistic effects and in the total relativistic value. Based on this analysis, we were able to study the electronic mechanism involved in a recently proposed relativistic effect, the "heavy atom effect on vicinal heavy atom" (HAVHA), in more detail. We found that the main electronic mechanism is the spin-orbit or σ T(3) correction, although other corrections p such as σ S(1) and σ S(3) are also important. Finally, we analyzed p p proton magnetic shieldings and found that, for molecules containing Sn as the central atom, σ(H) decreases as the number of heavy halogen substituents (of the same type: either F, Cl, or Br) increases, albeit at different rates for different halogens. σ(H) only increase as the number of halogen substituents increases if the halogen is iodine.